Applying the health capability profile to empirically study chronic hepatitis B in rural Senegal: a social justice mixed-methods study protocol. Issue 4 (11th April 2022) - Coste, Marion; Badji, Mouhamed Ahmed; Diallo, Aldiouma; Mora, Marion; Boyer, Sylvie; Prah, Jennifer J
Abstract : Introduction: Despite the early implementation of hepatitis B vaccination and the ongoing decentralisation of chronic hepatitis B (CHB) care, over 10% of the Senegalese adult population lives with CHB and liver cancer remains a main cause of death. Investigating factors associated with CHB infection, prevention of CHB-related morbidity, and prevention and treatment of mortality secondary to CHB calls for a holistic and multidimensional approach. This paper presents the adaptation of the health capability profile (HCP) to a specific epidemiological issue and empirical setting: it seeks to identify and analyse inter-related abilities and conditions (health capabilities) in relation to the CHB epidemic in the rural area of Niakhar, Senegal. Methods and analysis: This ongoing study relies on a sequential social justice mixed-methods design. The HCP is comprehensively adapted to CHB in rural Senegal and guides the design and conduct of the study. Objective and subjective data are collected at the individual level following a mixed-methods explanatory core design. The quantitative module, embedded in the ANRS12356 AmBASS cross-sectional survey (exhaustive sampling), is used to select a purposeful sampling of participants invited for one-on-one qualitative interviews. Additional data are collected at the institutional and community level through health facility surveys and an ethnography (in-depth interviews) of local and national CHB stakeholders. Data analysis adopts a synergistic approach to produce a multilayered analysis of individual HCPs and crosscutting analysis of the 15 health capabilities. The data integration strategy relies on a mixed-methods convergent core design, and will use 0–100 health capability scores as well as flow diagrams to measure and characterise levels of development and interactions among health capabilities, respectively. Ethics and dissemination: This study was approved by Senegalese and French authorities. Results dissemination through local workshops and scientific publications aim at fuelling effective policy change towards CHB-related health capability.